Enterprise Innovation, Executive Experience and Internationalization Strategy: Evidence From High-Carbon Industrial Enterprises Versus Low-Carbon Industrial Enterprises in China - Cui, Shuangchang (Frontiers in Energy Research, 2022)
Industrial enterprises are the core subjects to reduce carbon emissions. Their innovations for low-carbon production are the key to determine the effect of carbon emission reduction. This paper examines the impact of executive experience, especially the overseas experience, on enterprise innovations across 3559 enterprises in low-carbon, medium-carbon and high-carbon industries respectively. Interestingly, it shows that the executive experience has only played a significant role in enterprise innovations of high-carbon industrial enterprises, indicating that the executive’s international vision might help to promote innovation in high-carbon industry. Then, it’s also discovered that there is a mediating effect of international strategy which helps to better understand the impact mechanism of executive experience on enterprise innovation in high-carbon industry.